The Experimental overactive bladder modelling - O. I. Iatsyna; R. S. Vastyanov; I. M. Savytska; S. V. Vernygorodskyi (Kazimierz Wielki University, 2018)
An experimental study was conducted, which resulted in the development of a hyperactive urinary bladder model. Animals of the main group administered once daily for 14 days i.p. 0.3 ml of the hombiotensin, containing 0.45 mg of reserpine. This model development is confirmed by histological studies results. Morphological changes that arose in reproduction of the model of hyperactive bladder are determined by the following stages. Namely: compensatory hypertrophy of the wall with degenerative changes in smooth myocytes, disturbances of intercellular bonds due to the increase of immature collagen type 3 and type 4 in the early stages of observation (14 days), eventually leads to the depletion of adaptive capabilities with subsequent decompensation and sclerosis of the bladder wall at a late end of the experiment (28 days). The obtained model meets the requirements for qualitative indicators in the study of morphological changes in hyperactive urinary bladder model and can be used as a basis in the preclinical stage of research.